Gibberellic acid in the postharvest quality of ‘Nanicão’ banana - Fernandes Aquino, César; Chamhum Salomão, Luiz Carlos; Místico Azevedo, Alcinei; Alves Oliveira, João Alison (Comunicata Scientiae, 2020)
The article aimed to verify the effect of doses of gibberellic acid on the extension of postharvest life on ‘Nanicão’ bananas. The fruits were harvested in color stage 1 (completely green peel). A completely randomized design was used, in an arrangement of subdivided plots, with doses of GA3 allocated in the plots (0; 50; 100; 150 and 200 mg L-1) and evaluation times allocated in the subplots (0; 3; 6; 9, 12, 15, 19, 23, 27 and 31 days of storage), with four replications, with a bouquet of three fruits per sample unit. The bunches were stored in a refrigeration chamber of 22 ± 1 ºC and relative humidity of 91%. The study assessed fresh weight loss, peel color parameters, peel chlorophyll content, pulp firmness, soluble solids, titratable acidity, and CO2 production. The loss of fresh matter was lower in fruits treated with 200 mg L-1. Fruits treated with 200 mg L-1 had the highest Hue angle value (89.52). For the chlorophyll content, the highest doses favorably influenced the maintenance of the green color of the peel, delaying degradation. After 31 days of storage, the fruits treated with 200 mg L-1 of GA3 were firmer. The soluble solids content increased from 5.5 °Brix to 9.1 °Brix, from day zero until the 15th day of storage for all treatments. There was an increase in the titratable acidity content with the advance of ripening. The fruits of all treatments showed a typical respiratory pattern, regardless of the dose of GA3. After 31 days of storage, it was observed that the dose of 200 mg L-1 of GA3 was favorable to the postharvest conservation of the banana’ Nanicão.’